2003
DOI: 10.1007/s00464-002-8821-y
|View full text |Cite|
|
Sign up to set email alerts
|

Laparoscopic radiofrequency ablation and hepatic artery infusion pump placement in the evolving treatment of colorectal hepatic metastases

Abstract: LRFA and/or LHAIP placement are safe and feasible treatment options for the treatment of colorectal hepatic metastases. The choice of treatment for patients should be based primarily on tumor characteristics. Long-term studies, which will elucidate the role of these evolving treatments, are now under way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It has also been suggested that pump placement at the time of resection and/or RFA of liver metastases to facilitate adjuvant therapy may offer better hepatic tumor control and reduce the rate of hepatic recurrence. 11,17 Hepatic arterial pump chemotherapy normally requires a full laparotomy for placement of catheter and pump. Even though the reported morbidity associated with the open procedure is small, it is still considered less than desirable for this patient group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that pump placement at the time of resection and/or RFA of liver metastases to facilitate adjuvant therapy may offer better hepatic tumor control and reduce the rate of hepatic recurrence. 11,17 Hepatic arterial pump chemotherapy normally requires a full laparotomy for placement of catheter and pump. Even though the reported morbidity associated with the open procedure is small, it is still considered less than desirable for this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, there have been limited reports regarding this novel procedure, which include our own results. [10][11][12]19 The success of HAI therapy is dependent on careful patient selection and meticulous surgical technique. It is critically important that the distribution of chemotherapy reaches the entire liver without misperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A minimally invasive pump placement using conventional laparoscopic techniques has been described in the literature [9][10][11][12]. Franklin et al reported a series of 20 laparoscopic pump placements during concurrent major laparoscopic procedures with no conversions and no intraoperative complications [10].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, hepatic colorectal metastases are the leading cause of cancerrelated morbidity and mortality in Western society. 1 However, a minority (10-20%) of patients with hepatic colorectal metastases will be candidates for liver resection (reviewed Cheng et al, 4 and Kitamoto et al 5 ). In many of these patients, the liver is the only site of metastasis.…”
mentioning
confidence: 99%